"Drought isn't just water, it is living": Narratives of drought vulnerability in California's San Joaquin Valley. Issue 121 (May 2021) - Greene, Christina
Highlights: Narratives of drought reveal lived experiences and local climate knowledge. Local drought knowledge is embedded in timescales that include past, present, and desired futures. Drought vulnerability is contested, with implications for drought policies. Abstract: Drought vulnerability studies in the United States primarily focus on biophysical and economic indicators and overlook the multiple ways drought is experienced socially. This research examines the human dimensions of drought through narratives of drought vulnerability in the agricultural communities of California's San Joaquin Valley during the 2012–2016 drought. Four narratives are identified that reveal the lived experiences and local knowledges of drought as well as the multiple understandings of the political, economic, social, and environmental processes that produce drought vulnerability. The narratives explain the production of drought across long timescales that include both memories of historical events as well as visions of desired futures for the region. Who is vulnerable and why differs across the narratives, with each narrative offering competing understandings for how the relationships between water, agriculture, labor, and rural communities create drought vulnerability. Which narrative becomes dominant and embedded in water governance has impacts on the practice of agriculture as well as social and environmental justice for farmworkers and rural community members.